Evaluation of angulation and distance deviation for robot-guided laser osteotomy – a follow-up study on digital high-tech procedures - Msallem, Bilal; Veronesi, Lara; Halbeisen, Florian Samuel; Beyer, Michel; Dragu, Adrian; Thieringer, Florian Markus (Frontiers in Robotics and AI, 2025)
Background and objectiveConventional osteotomy tools, including drills and saws, have been associated with several limitations, such as restricted cutting geometry and the risk of heat-induced necrosis, which affects bone healing. Laser-based osteotomy systems have emerged as a promising solution for these constraints. This study aims to evaluate the accuracy of robot-guided laser osteotomy compared to conventional cutting-guided osteotomy based on surface scanning.Materials and methodsTen 3D printed mandibular models were used to perform segmentectomy. Five models were treated with conventional osteotomies employing a cutting-guided saw technique, while the remaining five were subjected to laser osteotomy. Initially conducted using root mean square (RMS) values, the analysis has been expanded to reevaluate the angulation and distance deviation outcomes.ResultsPrecision analysis of the upper cutting plane revealed a statistically significant difference in distance deviation between the laser osteotomy group (0.48 mm) and the conventional osteotomy group (0.78 mm). In terms of angulation deviation, the laser osteotomy group exhibited, both in the upper and lower cutting planes, statistically significant results (2.19° and 2.86°) compared to the osteotomy group (5.15° and 8.12°).ConclusionBased on the observed angulation and distance deviations, it can be concluded that robot-guided laser systems achieve significantly higher accuracy in osteotomies than conventional cutting-guided systems currently available. Consistent with the findings of a prior study, these results confirm that robot-guided laser osteotomy provides substantial advantages, facilitating the seamless integration of precise virtual preoperative planning with exact execution in the human body.